Cytokine Adsorption in Critically Ill Patients Requiring ECMO Support - Lother, Achim; Benk, Christoph; Staudacher, Dawid L.; Supady, Alexander; Bode, Christoph; Wengenmayer, Tobias; Duerschmied, Daniel (Frontiers in Cardiovascular Medicine, 2019)
Systemic inflammation is a key characteristic of sepsis but also in non-infectious conditions such as post-cardiac arrest syndrome. Cytokine adsorption and extracorporeal membrane oxygenation are emerging therapies applied in these critically ill patients, but the experience with their concurrent use is limited. We evaluated cytokine adsorption in critically ill patients requiring support with either veno-venous (vv) or veno-arterial (va) extracorporeal membrane oxygenation (ECMO) support and hypothesized that adsorber incorporation into the ECMO circuit was technically feasible and not associated with imminent risk. We analyzed data from the first six cases of a prospective single-center registry of patients undergoing veno-venous (vv) or veno-arterial (va) ECMO therapy. While in most published cases cytokine adsorbers were inserted into a hemofiltration circuit, we directly incorporated the adsorber into the ECMO circuit without interruption of continuous ECMO support. We observed no relevant side effects attributable to cytokine adsorption. Thirty-day mortality was 83% (predicted mortality 87%), indicating that the decision for adding cytokine adsorption may have been considered as an ultima ratio decision in severe cases with poor prognosis. Vasopressor or inotrope use, lactate level, and fluid balance did not change significantly when comparing pre- versus post-cytokine adsorption values. Interestingly, the real-time course of the mentioned three surrogate parameters remained unaltered in all but two cases, regardless of cytokine removal. Beneficial effects of cytokine adsorption are plausible in two va-ECMO-treated patients, where increasing lactate began to drop after initiation of cytokine adsorption. Taken together, these data suggest that incorporation of cytokine adsorption into the management of critically ill patients requiring continued ECMO support is feasible and easy to handle. Whether cytokine removal improves clinical outcome in ECMO-treated patients should now be investigated in randomized controlled trials.